Contribution of Mitophagy to Cell‐Mediated Mineralization: Revisiting a 50‐Year‐Old Conundrum. Issue 10 (29th July 2018) - Pei, Dan‐dan; Sun, Jin‐long; Zhu, Chun‐hui; Tian, Fu‐cong; Jiao, Kai; Anderson, Matthew R.; Yiu, Cynthia; Huang, Cui; Jin, Chang‐xiong; Bergeron, Brian E.; Chen, Ji‐hua; Tay, Franklin R.; et al.
Abstract: Biomineralization in vertebrates is initiated via amorphous calcium phosphate (ACP) precursors. These precursors infiltrate the extracellular collagen matrix where they undergo phase transformation into intrafibrillar carbonated apatite. Although it is well established that ACP precursors are released from intracellular vesicles through exocytosis, an unsolved enigma in this cell‐mediated mineralization process is how ACP precursors, initially produced in the mitochondria, are translocated to the intracellular vesicles. The present study proposes that mitophagy provides the mechanism for transfer of ACP precursors from the dysfunctioned mitochondria to autophagosomes, which, upon fusion with lysosomes, become autolysosomes where the mitochondrial ACP precursors coalesce to form larger intravesicular granules, prior to their release into the extracellular matrix. Apart from endowing the mitochondria with the function of ACP delivery through mitophagy, the present results indicate that mitophagy, triggered upon intramitochondrial ACP accumulation in osteogenic lineage‐committed mesenchymal stem cells, participates in the biomineralization process through the BMP/Smad signaling pathway. Abstract : Mitochondria contribute to cell‐mediated biomineralization by delivery of mineralizing precursors through mitophagy. It is proposed that mitophagy provides the mechanism for transfer of amorphous calcium phosphate (ACP) precursors from the dysfunctioned mitochondria to autophagosomes, which upon fusion with lysosomes become autolysosomes where the mitochondrial ACP precursors coalesce to form larger intravesicular granules, prior to their release into the extracellular matrix.